Climate Change Interactive Teaching Materials to Enhance Students' Critical Thinking Skills and Science Attitude - Indarini Dwi Pursitasari; Bibin Rubini; Muhammad Iqbal Suriansyah; Siti Samsia; Nila Puspita (Postgraduate, University of Mataram, 2023)
The skills needed in the 21st century are basic literacy, competence, and character. Critical thinking skills are one of the competencies and attitudes of science which is part of the character. The research aims to enhance students' critical thinking skills and science attitudes using interactive teaching materials on Climate Change. This quasi-experimental research was conducted in one of the junior high schools in Bogor involving 42 students in the experimental class and 41 students in the control class. Data collection uses critical thinking skills tests in the form of essays, science attitude questionnaires, and student response questionnaires. The data collected were analyzed descriptively and inferentially. The results showed that students who used interactive teaching materials had a higher average N-gain than the control class. The results of the t-test show that there are significant differences in critical thinking skills. The students' scientific attitude showed a meaning that was not much difference between students who used interactive teaching materials and those without them. Students gave a positive response to climate change interactive teaching materials in science learning.